Comparative Literature and China : Methods and Perspectives - Lu, Sheldon,; Zhang, Longxi, (Literature and Cultural Studies E-Books Online, Collection 2026., 2026)
This book aims at an exploration of Chinese literary studies in comparative, cross-cultural, transnational, and global contexts. It is one of the first of its kind in dealing with methodological and theoretical issues regarding Chinese, comparative, and world literature in recent years. Contributors explore the fundamentals: the history and development of comparative literature as an academic discipline; the methodology of comparative literature and cross-cultural comparison; comparative poetics; the place of Chinese literature in the world and the relationship between Chinese literature and world literature; the role of translation in the intercultural reception of literary works; canon formation in world literature; comparative study of literary genres such as the lyric and the novel. Contributors: Chung-An Chang, Daniel Fried, Haomin Gong, Jian Guo, Elizabeth Harper, Wen Jin, Lucas Klein, Liu Yan, Sheldon Lu, Haun Saussy, Zhang Longxi, Zhen Zhang